2018
DOI: 10.1002/esp.4367
|View full text |Cite
|
Sign up to set email alerts
|

Excavation of subglacial bedrock channels by seasonal meltwater flow

Abstract: Subglacial water flow drives the excavation of a variety of bedrock channels including tunnel valleys and inner gorges. Subglacial floods of various magnitudes – events occurring once per year or less frequently with discharges larger than a few hundred cubic metres per second – are often invoked to explain the erosive power of subglacial water flow. In this study we examine whether subglacial floods are necessary to carve bedrock channels, or if more frequent melt season events (e.g. daily production of meltw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 87 publications
(290 reference statements)
1
26
1
Order By: Relevance
“…Persistent subglacial water routing may incise channels into the underlying bedrock (Nye or N-channels; Figure 4; Nye, 1976). On the basis that surface-to-bed connections seem to form in the same locations year-to-year (e.g., Clason et al, 2015) and that channels incised into bedrock have been observed in deglaciated regions (e.g., Walder and Hallet, 1979;Sharp et al, 1989), we think it is likely that N-channels exist in some locations beneath the ice sheet (e.g., Beaud et al, 2018) and may provide preferential flow pathways. Water flow along water-filled Nchannels will melt the overlying ice, possibly forming an N-Rchannel hybrid (i.e., a channel partially melted into the overlying ice and partially eroded into bedrock).…”
Section: Conceptualised Subglacial Drainage Morphologiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Persistent subglacial water routing may incise channels into the underlying bedrock (Nye or N-channels; Figure 4; Nye, 1976). On the basis that surface-to-bed connections seem to form in the same locations year-to-year (e.g., Clason et al, 2015) and that channels incised into bedrock have been observed in deglaciated regions (e.g., Walder and Hallet, 1979;Sharp et al, 1989), we think it is likely that N-channels exist in some locations beneath the ice sheet (e.g., Beaud et al, 2018) and may provide preferential flow pathways. Water flow along water-filled Nchannels will melt the overlying ice, possibly forming an N-Rchannel hybrid (i.e., a channel partially melted into the overlying ice and partially eroded into bedrock).…”
Section: Conceptualised Subglacial Drainage Morphologiesmentioning
confidence: 98%
“…However, observations of the subglacial environment and constraints on crucial model parameters are sparse, leading to uncertainty in inferences from models: modelled R-channels can form under conditions representative of the upper ablation area if a large (∼1 m 2 ) initial conduit size is used (e.g., Hewitt, 2011;Gulley et al, 2012). Such conditions may occur due to uplift during rapid lake drainage (Das et al, 2008;Pimentel and Flowers, 2010;Andrews et al, 2018) or may be facilitated if persistent surface-to-bed hydrological connections (Catania and Neumann, 2010) enable erosion of preferential flow pathways into the substrate (Gulley et al, 2012;Beaud et al, 2018). In addition, the spatial pattern of surfaceto-bed connections (moulins) strongly influences the spatial organisation of modelled subglacial channels, with a high density of moulins producing widespread and rapid channelisation beneath ice up to 815 m thick (Banwell et al, 2016).…”
Section: Efficient Channel Formationmentioning
confidence: 99%
“…Subglacial flood flows are often invoked in order to explain the erosive power of water (Kehew et al, 2012;Wright, 1973;van der Vegt et al, 2012), the size of clasts found in eskers, or the large changes in flow regimes inferred from esker sediment (e.g., Brennand, 1994;Burke et al, 2012). Recent numerical modeling studies, however, suggest that pressurized seasonal meltwater flow produces sufficient shear stresses to transport boulder-size clasts and erode the bedrock (Beaud et al, 2016(Beaud et al, , 2018. The formation of eskers has been attributed to either the geology of the substrate (Clark & Walder, 1994), the availability of meltwater (e.g., Storrar et al, 2014), or the availability of sediment (e.g., Burke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Booth and Hallet, 1993; Kehew and others, 2012; Atkinson and others, 2013; Kearsey and others, 2018). Recent work on occurrence and causes of narrow canyons incised into the floors of glacial troughs (‘inner gorges’) in the Swiss Alps and Scandinavia also argues for vigorous and relatively extensive subglacial fluvial erosion (Dürst-Stucki and others, 2012; Jansen and others, 2014; Beaud and others, 2018). As additional geophysical and borehole data have been collected, buried inner gorges have been identified.…”
Section: Erosive Processes – Some Recent Insightsmentioning
confidence: 99%